2022
DOI: 10.20944/preprints202206.0150.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Creating a Re-Tech Theme Park through the Neuromarketing and Cartoon Characters

Abstract: Renewable energy technologies (RET) are critical to the sustainable development of modern societies. Hong Kong has set up a RET theme park so as to fulfill the needs of and impart knowledge on RET through entertainment and educational activities. Such understanding aids in formulating appropriate future park designs and neuromarketing strategies to maximize the attractiveness of the park. Therefore, this study attempts to investigate potential visitors’ preferences with regard to cartoon characters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These factors entail the essential requirements that need to be considered for a theme park ride to be a tourist magnet. Bu et al (2022) revealed that movies characters (e.g. Mickey Mouse, Shrek, Hello Kitty, among many others) are necessary elements of theme park designs to meet visitors' needs.…”
Section: Data Collectionmentioning
confidence: 99%
“…These factors entail the essential requirements that need to be considered for a theme park ride to be a tourist magnet. Bu et al (2022) revealed that movies characters (e.g. Mickey Mouse, Shrek, Hello Kitty, among many others) are necessary elements of theme park designs to meet visitors' needs.…”
Section: Data Collectionmentioning
confidence: 99%